ECG is an inefficient screening-tool for left ventricular hypertrophy in normotensive African children population - Di Gioia, Giuseppe; Creta, Antonio; Campanale, Cosimo Marco; Fittipaldi, Mario; Giorgino, Riccardo; Quintarelli, Fabio; Satriano, Umberto; Cruciani, Alessandro; Antinolfi, Vincenzo; Di Berardino, Stefano; Costanzo, Davide; Bettini, Ranieri; et al. (PeerJ, 2016)
Background Left ventricular hypertrophy (LVH) is a marker of pediatric hypertension and predicts development of cardiovascular events. Electrocardiography (ECG) screening is used in pediatrics to detect LVH thanks to major accessibility, reproducibility and easy to use compared to transthoracic echocardiography (TTE), that remains the standard technique. Several diseases were previously investigated, but no data exists regarding our study population. The aim of our study was to evaluate the relationship between electrocardiographic and echocardiographic criteria of LVH in normotensive African children. Methods We studied 313 children (mean age 7,8 ± 3 yo), in north-Madagascar. They underwent ECG and TTE. Sokolow-Lyon index was calculated to identify ECG-LVH (>35 mm). Left ventricle mass (LVM) with TTE was calculated and indexed by height2.7 (LVMI2.7) and weight (LVMIw). We report the prevalence of TTE-LVH using three methods: (1) calculating percentiles age- and sex- specific with values >95th percentile identifying LVH; (2) LVMI2.7 >51 g/m2.7; (3) LVMIw >3.4 g/weight. Results 40 (13%) children showed LVMI values >95th percentile, 24 children (8%) an LVMI2.7 >51 g/m2.7 while 19 children (6%) an LVMIw >3.4 g/kg. LVH-ECG by Sokolow-Lyon index was present in five, three and three children respectively, with poor values of sensitivity (ranging from 13 to 16%), positive predictive value (from 11 to 18%) and high values of specificity (up to 92%). The effects of anthropometrics parameters on Sokolow-Lyon were analyzed and showed poor correlation. Conclusion ECG is a poor screening test for detecting LVH in children. In clinical practice, TTE remains the only tool to be used to exclude LVH.
Keywords: ECG; Ventricular hypertrophy; Screening; African children